2012
DOI: 10.1007/s00268-012-1587-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative α‐Fetoprotein Level on Disease‐Free Survival After Liver Transplantation for Hepatocellular Carcinoma

Abstract: This study shows the prognostic value of preoperative AFP levels on DFS after a liver transplant for HCC in a population of patients undergoing transplantation with the same preoperative criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…In fact, Yao et al [62] in California require that patients with an initial AFP > 1000 ng/mL have AFP decreased to < 500 ng/mL after loco regional therapy, before undergoing LT. Similarly, in Yamashiki et al [43] 2004 93 United States Prospective 100 ng/mL Drop-out from list Shetty et al [42] 2004 109 United States Retrospective 300 ng/mL Recurrence, death Todo et al [54] 2007 653 Japan Retrospective 200 ng/mL Recurrence 1000 ng/mL Parfitt et al [61] 2007 75 Canada Retrospective 1000 ng/mL Recurrence Pérez-Saborido et al [44] 2007 95 Spain Retrospective 200 ng/mL Recurrence Onaca et al [10] 2007 902 United States Retrospective 200 ng/mL Recurrence Adler et al [86] 2008 226 Belgium Retrospective 100 ng/mL Recurrence Zou et al [45] 2008 303 China Retrospective 1000 ng/mL Fatal recurrence Ioannou et al [50] 2008 5028 United States Retrospective 455 ng/mL Death Xu et al [46] 2009 97 China Retrospective 400 ng/mL Recurrence Toso et al [49] 2009 6478 Canada Retrospective 400 ng/mL Death Lao et al [55] 2009 124 United States Prospective 1000 ng/mL Recurrence Xiao et al [87] 2009 224 China Retrospective 800 ng/mL Death McHugh et al [47] 2010 101 United States Retrospective 100 ng/mL Recurrence, death Levi et al [88] 2010 244 United States Retrospective 100 ng/mL Recurrence Merani et al [66] 2011 6817 United States Retrospective 400 ng/mL Death Lai et al [89] 2011 153 Italy Retrospective 210 ng/mL Recurrence Mailey et al [48] 2011 2253 United States Retrospective 400 ng/mL Death Muscari et al [28] 2012 122 France Retrospective 500 ng/mL Recurrence, death Ciccarelli et al [65] 2012 137 Belgium Retrospective 400 ng/mL Recurrence Wong et al [59] 2013 211 United States Retrospective 400 ng/mL Recurrence Harimoto et al [90] 2013 167 Japan Retrospective 300 ng/mL Recurrence Abdel-Wahab et al [68] 2013 170 Egypt Retrospective 200 ng/mL Recurrence, death Grąt et al [67] 2014 121 Poland Retrospective 100 ng/mL Recurrence Hameed et al [30] 2014 211 United States Retrospective 1000 ng/mL Microvascular invasion Lee et al [91] 2014 69 South Korea Retrospective 200 ng/mL Recurrence Grąt et al [...…”
Section: Evolution Of Afp Over Time: a Critical Markermentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Yao et al [62] in California require that patients with an initial AFP > 1000 ng/mL have AFP decreased to < 500 ng/mL after loco regional therapy, before undergoing LT. Similarly, in Yamashiki et al [43] 2004 93 United States Prospective 100 ng/mL Drop-out from list Shetty et al [42] 2004 109 United States Retrospective 300 ng/mL Recurrence, death Todo et al [54] 2007 653 Japan Retrospective 200 ng/mL Recurrence 1000 ng/mL Parfitt et al [61] 2007 75 Canada Retrospective 1000 ng/mL Recurrence Pérez-Saborido et al [44] 2007 95 Spain Retrospective 200 ng/mL Recurrence Onaca et al [10] 2007 902 United States Retrospective 200 ng/mL Recurrence Adler et al [86] 2008 226 Belgium Retrospective 100 ng/mL Recurrence Zou et al [45] 2008 303 China Retrospective 1000 ng/mL Fatal recurrence Ioannou et al [50] 2008 5028 United States Retrospective 455 ng/mL Death Xu et al [46] 2009 97 China Retrospective 400 ng/mL Recurrence Toso et al [49] 2009 6478 Canada Retrospective 400 ng/mL Death Lao et al [55] 2009 124 United States Prospective 1000 ng/mL Recurrence Xiao et al [87] 2009 224 China Retrospective 800 ng/mL Death McHugh et al [47] 2010 101 United States Retrospective 100 ng/mL Recurrence, death Levi et al [88] 2010 244 United States Retrospective 100 ng/mL Recurrence Merani et al [66] 2011 6817 United States Retrospective 400 ng/mL Death Lai et al [89] 2011 153 Italy Retrospective 210 ng/mL Recurrence Mailey et al [48] 2011 2253 United States Retrospective 400 ng/mL Death Muscari et al [28] 2012 122 France Retrospective 500 ng/mL Recurrence, death Ciccarelli et al [65] 2012 137 Belgium Retrospective 400 ng/mL Recurrence Wong et al [59] 2013 211 United States Retrospective 400 ng/mL Recurrence Harimoto et al [90] 2013 167 Japan Retrospective 300 ng/mL Recurrence Abdel-Wahab et al [68] 2013 170 Egypt Retrospective 200 ng/mL Recurrence, death Grąt et al [67] 2014 121 Poland Retrospective 100 ng/mL Recurrence Hameed et al [30] 2014 211 United States Retrospective 1000 ng/mL Microvascular invasion Lee et al [91] 2014 69 South Korea Retrospective 200 ng/mL Recurrence Grąt et al [...…”
Section: Evolution Of Afp Over Time: a Critical Markermentioning
confidence: 99%
“…In the following years, multiple studies have confirmed the prognostic role of AFP to predict outcomes after LT. Most of them are based on small cohorts of patients [28,4347] and their main drawbacks are their retrospective designs. Yet all of them display the same tendency: Elevated AFP at the time of LT is associated with a worse prognosis after LT.…”
Section: Afp: a Predictor Of Recurrence After Ltmentioning
confidence: 99%
“…Higher tumor recurrence Mailey et al [22] Low (≤ 20) Mediun and high: Higher mortality Mediun High (≥ 400) Muscari et al [23] DFS Recurrence Normal 71% 4% 10-150 75% 10% 150-500 57% 24% > 500 46% 62% Chiao et al [24] > 1.000…”
Section: Importancementioning
confidence: 99%
“…In a multivariate analysis, the medium and high AFP groups were associated with higher mortality. Another study [23] correlated the DFS and 5-year recurrence rate to the AFP level. Normal AFP values between 10-150 ng/mL, those from 150-500 ng/mL and those > 500 reduce DFS from 71% to 57%, 46% and 28%, respectively, and increase the recurrence rate from 4% to 10%, 24% and 62%, respectively.…”
Section: Isolated Biological Criteria For the Selection And Prognosismentioning
confidence: 99%
“…Extended criteria [9,10,11] have aimed to improve the selection of appropriate LT recipients among patients with advanced HCC; however, most of these classifications are also primarily based on morphological characteristics rather than on assessments of tumor aggressiveness and have failed to be generally accepted. Tumor biology has been shown to correlate with clinicopathological variables including tumor differentiation, the presence of microvascular tumor invasion, and α-fetoprotein (AFP) levels [12,13,14,15]. However, only AFP can be easily obtained before LT and thus support patient selection, whereas microvascular invasion and tumor grading cannot be reliably assessed prior to the recipient hepatectomy [16].…”
Section: Introductionmentioning
confidence: 99%